Homology-directed repair is a major double-strand break repair pathway in mammalian cells - Liang, Feng (The National Academy of Sciences, 1998)
Mammalian cells have been presumed to repair potentially lethal chromosomal double-strand breaks (DSBs) in large part by processes that do not require homology to the break site. This contrasts with Saccharomyces cerevisiae where the major DSB repair pathway is homologous recombination. Recently, it has been determined that DSBs in genomic DNA in mammalian cells can stimulate homologous recombination as much as 3 or 4 orders of magnitude, suggesting that homology-directed repair may play an important role in the repair of chromosomal breaks. To determine whether mammalian cells use recombinational repair at a significant level, we have analyzed the spectrum of repair events at a defined chromosomal break by using direct physical analysis of repair products. When an endonuclease-generated DSB is introduced into one of two direct repeats, homologous repair is found to account for 30–50% of observed repair events. Both noncrossover and deletional homologous repair products are detected, at approximately a 1:3 ratio. These results demonstrate the importance of homologous recombination in the repair of DSBs in mammalian cells. In the remaining observed repair events, DSBs are repaired by nonhomologous processes. The nonhomologous repair events generally result in small deletions or insertions at the break site, although a small fraction of events result in larger chromosomal rearrangements. Interestingly, in two insertions, GT repeats were integrated at one of the broken chromosome ends, suggesting that DSB repair can contribute to the spread of microsatellite sequences in mammalian genomes.